Legal Analysis of Judges Considerations in Determining Criminal Responsibility in Cases of Assault Resulting in Death - Fitria Ramadhani Siregar; T. Riza Zarzani; Okta Priani Br Surbakti (Yayasan Multidimensi Kreatif, 2024)
This study analyzes the judge's considerations in determining criminal liability in cases of assault resulting in death. The focus of the study is to examine the aspects that form the basis for the judge's considerations in determining the element of guilt, proof of intent, and application of criminal sanctions. This study uses a normative legal method with a statute approach and a case approach. Primary data were obtained from court decisions related to assault cases resulting in death at the Medan District Court for the 2020-2023 period, while secondary data came from laws and regulations, books, legal journals, and related literature. The results of the study show that in determining criminal liability, judges consider several crucial aspects: (1) proof of the element of intent in acts of assault which is different from intent in premeditated murder, (2) the causal relationship between the act of assault and the victim's death, (3) aggravating and mitigating factors, and (4) aspects of justice, legal certainty, and benefit in the application of sanctions. The study also found variations in the application of criminal sanctions, with the average sentence handed down ranging from 7-12 years in prison, depending on the severity of the abuse and other accompanying factors. The theoretical implications of this study contribute to the development of the doctrine of criminal liability in cases of abuse resulting in death, while its practical implications provide a reference for judges in considering the elements of criminal liability in similar cases.